2014
DOI: 10.1007/s11096-014-9918-9
|View full text |Cite
|
Sign up to set email alerts
|

Results of intravitreal triamcinolone acetonide in patients with macular edema secondary to branch retinal vein occlusion

Abstract: Intravitreal triamcinolone, due to absence of systemic side effects, can be used with confidence for treatment macular edema secondary to BRVO. However the main disadvantages of intravitreal triamcinolone injection are elevation of intraocular pressure and formation of cataract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…Research has demonstrated that both 3-month intravitreal injections of an anti-VEGF agent bevacizumab and two IVTA injections 2 months apart could be effective in respect to both visual and anatomical outcomes [125]. TA has much lower prices but has a higher rate of adverse events like increased intraocular pressure (IOP), cataract progression, and sterile pseudoendophthalmitis [101, 124, 126130]. The SCORE study ( n = 411) showed that the outcome of IVTA 1 mg groups is similar to IVTA 4 mg groups and can lower the rate of adverse events [131].…”
Section: Treatmentmentioning
confidence: 99%
“…Research has demonstrated that both 3-month intravitreal injections of an anti-VEGF agent bevacizumab and two IVTA injections 2 months apart could be effective in respect to both visual and anatomical outcomes [125]. TA has much lower prices but has a higher rate of adverse events like increased intraocular pressure (IOP), cataract progression, and sterile pseudoendophthalmitis [101, 124, 126130]. The SCORE study ( n = 411) showed that the outcome of IVTA 1 mg groups is similar to IVTA 4 mg groups and can lower the rate of adverse events [131].…”
Section: Treatmentmentioning
confidence: 99%
“…Triamcinolone and other corticosteroids have clinically been applied as intravitreal application for the therapy of many intraocular edematous diseases such as diabetic macular edema and retinal vein occlusions. [79][80][81][82][83][84] Chinese medicinal herbs have also been reported to have an effect on activated microglia. 85 Scutellarin is a natural flavone glucuronide which is extracted from Erigeron breviscapus.…”
Section: Microglia-targeted Therapymentioning
confidence: 99%
“…Demir ve ark. (21) ven dal oklüzyonuna bağlı maküla ödemi tedavisinde İVTA sonrası %18,75 oranında katarakt oluşumu gözlemişlerdir. Krepler ve ark.…”
Section: Discussionunclassified